Study protocol for a multicentre nationwide prospective cohort study to investigate the natural course and clinical outcome in benign liver tumours and cysts in the Netherlands: the BELIVER study. Issue 9 (8th September 2022) - Furumaya, Alicia; Haring, Martijn P D; van Rosmalen, Belle V; Klompenhouwer, Anne J; Besselink, Marc G; de Man, Robert A; IJzermans, Jan N M; Thomeer, Maarten G J; Kramer, Matthijs; Coolsen, Mariëlle M E; Tushuizen, Maarten E; Schaapherder, Alexander F; et al.
Abstract : Introduction: Benign liver tumours and cysts (BLTCs) comprise a heterogeneous group of cystic and solid lesions, including hepatic haemangioma, focal nodular hyperplasia and hepatocellular adenoma. Some BLTCs, for example, (large) hepatocellular adenoma, are at risk of complications. Incidence of malignant degeneration or haemorrhage is low in most other BLTCs. Nevertheless, the diagnosis BLTC may carry a substantial burden and patients may be symptomatic, necessitating treatment. The indications for interventions remain matter of debate. The primary study aim is to investigate patient-reported outcomes (PROs) of patients with BLTCs, with special regards to the influence of invasive treatment as compared with the natural course of the disease. Methods and analysis: A nationwide observational cohort study of patients with BLTC will be performed between October 2021 and October 2026, the minimal follow-up will be 2 years. During surveillance, a questionnaire regarding symptoms and their impact will be sent to participants on a biannual basis and more often in case of invasive intervention. The questionnaire was previously developed based on PROs considered relevant to patients with BLTCs and their caregivers. Most questionnaires will be administered by computerised adaptive testing through the Patient-Reported Outcomes Measurement Information System. Data, such as treatment outcomes, will be extracted from electronic patient files. Multivariable analysis will be performed to identify patient and tumour characteristics associated with significant improvement in PROs or a complicated postoperative course. Ethics and dissemination: The study was assessed by the Medical Ethics Committee of the University Medical Center Groningen and the Amsterdam UMC. Local consultants will provide information and informed consent will be asked of all patients. Results will be published in a peer-reviewed journal. Study registration: NL8231—10 December 2019; Netherlands Trial Register.